2007
DOI: 10.1021/ac701606g
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Spores for Portable Bacterial Whole-Cell Biosensing Systems

Abstract: Whole-cell sensing systems based on living genetically engineered bacteria are known to have high sensitivity, selectivity, and rapid response times. Although these systems have found applications in biomedical and environmental analyses, their limited shelf life and transportability still restrict their use for on-site monitoring of analytes. To that end, we have developed a new method for the long-term preservation, storage, and transport of whole-cell biosensing systems that is based on bacterial spores, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…These dormant highly resistant cells can easily differentiate into responding cells after a germination step. As a matter of fact, while this work was in progress, the ability of spore-based systems to retain their detection properties was investigated [Date et al, 2007]. The authors showed that spores were effectively able to retain their analytical performance (in terms of detection limit, dynamic range and reproducibility) after either a long storage period or several cycles of germination/sporulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dormant highly resistant cells can easily differentiate into responding cells after a germination step. As a matter of fact, while this work was in progress, the ability of spore-based systems to retain their detection properties was investigated [Date et al, 2007]. The authors showed that spores were effectively able to retain their analytical performance (in terms of detection limit, dynamic range and reproducibility) after either a long storage period or several cycles of germination/sporulation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, colorimetric assay is highly recommended because no special tool is required to detect, at least qualitatively, the color of the product of the reaction. Immobilizing bacteria or the use of spores were proposed as issues regarding robustness problems [Date et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The natural ability of some microorganisms to form highly resilient spores can also be taken advantage of as a long-term storage solution. Date et al [14] converted spore-forming Bacillus cells into bioreporters with shelf-lives of up to 8 months, and further showed that they could be repeatedly cycled between their active and dormant states with little ancillary effect on their sensing capabilities.…”
Section: Bioreporter Immobilization Methodsmentioning
confidence: 99%
“…A number of reports have described the use of B. subtilis in biosensors. Luciferase-based biosensors have been reported for arsenic, antimony, cadmium and lead (Tauriainen et al 1997(Tauriainen et al , 1998, and β-galactosidase-based chemiluminescent and chromogenic endospore biosensors for arsenic, bacitracin and zinc (Date et al 2007(Date et al , 2010. We have previously reported an endospore-based arsenic biosensor with a chromogenic visual response for easy detection in the field and are currently involved in a collaboration to develop an improved version of this (Arsenic Biosensor Collaboration 2013).…”
Section: Chassis Considerationsmentioning
confidence: 99%